2004
DOI: 10.1159/000076591
|View full text |Cite
|
Sign up to set email alerts
|

Our Experience with Nifedipine and Prednisolone as Expulsive Therapy for Ureteral Stones

Abstract: Objectives: We evaluated the effect of nifedipine associated with prednisolone in ureteral stone passage. Material and Methods: In our department we enrolled 50 patients with radiopaque ureteral stones. Stone size was 15 mm or less. The patients were divided into two groups: group I included 25 patients who received 30 mg oral treatment of slow – release nifedipine (for a maximum of 20 days) and 25 mg of prednisolone (for a maximum of 10 days) daily. Group II was made up of 25 patients who received 25 mg of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 8 publications
2
37
0
Order By: Relevance
“…3,4 In the review by Hollingsworth and colleagues, the results of MET administered with calcium channel blockers and alpha blockers were evaluated in 9 randomized, controlled studies. When compared with the control groups, these agents caused 65% more spontaneous passage of stones.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 In the review by Hollingsworth and colleagues, the results of MET administered with calcium channel blockers and alpha blockers were evaluated in 9 randomized, controlled studies. When compared with the control groups, these agents caused 65% more spontaneous passage of stones.…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Saita and colleagues and Borghi and colleagues both demonstrated clinical significance in increasing expulsion rates of distal ureteral stones in patients who received combined methylprednisolone and nifedipine therapy. 19,20 No significant side effects were described in either study.…”
Section: Corticosteroidsmentioning
confidence: 78%
“…Alpha-blockers have been described to be significantly better than nifedipine in facilitating stone passage and relieving renal colic. 19,17,21 As a result, the most recent EAU guidelines do not recommend calcium channel blockers as a monotherapy for MET. 2 However, it may be safely used in conjunction with alpha-blockers in the appropriate patient population as side effects have been found to be insignificant.…”
Section: Calcium Channel Blockersmentioning
confidence: 99%
“…One study by Saita (2004) All studies that examined corticosteroids treated distal ureteral stones only, except one study that examined all ureteral stones. Most studies included radiopaque stones only which lead to a gap in knowledge about corticosteroids for non-radiopaque stones like cystine and uric acid stones [39].…”
Section: Discussionmentioning
confidence: 99%